Entrepreneurship, Growth, and Public Policy - Ács, Zoltán J.; Audretsch, David B.; Strom, Robert J.; Kauffman-Max Planck Summit on Enterpreneurship Research and Policy (Cambridge University Press, 2009)
While the public policy community has turned to entrepreneurship to maintain, restore, or generate economic prosperity, the economics profession has been remarkably taciturn in providing guidance for public policy for understanding the links between entrepreneurship and economic growth as well as for framing and weighing policy issues and decisions. The purpose of this volume is to provide a lens through which public policy decisions involving entrepreneurship can be guided and analyzed. In particular, this volume provides insights from leading research concerning the links between entrepreneurship, innovation, and economic growth that shed light on implications for public policy. The book makes clear both how and why small firms and entrepreneurship have emerged as crucial to economic growth, employment, and competitiveness as well as the mandate for public policy in the entrepreneurial society.